Phonological Variation in Serawai Language Used by Minangkabaunese and Serawainese in Kota Manna, South Bengkulu. - Lydia Gustina; Nadra Nadra; Rina Marnita (JURNAL ARBITRER, 2018)
This research aims to describe the phonological variation in Serawai language used by Minangkabaunese and Serawainese. This research is a descriptive research with a qualitative approach. The method that used in this research is method that proposed by Sudaryanto. The data are collected by using observational method, the technique applied in collecting data are interview, recording and taking field notes. In analyzing data, the researcher used a distributional method. The presenting the result is by using formal (signs and symbols) and informal method (descriptive of ordinary word). The result of this research is the phonological variation in Serawai language that used by Minangkabaunese and Serawainese consist of 8 differential. They are 4 vocoid variations and 4 contoid variations. The vocoid variations are [ə]~[e], [i]~[e], [u]~[o], and [a:]~[a]. The contoid variations are [w]~[Ø], [y]~[Ø], [b]~[Ø], and [ɤ]~r]. There are phonologycal variations in Serawai language that used by Minangkabaunese and Serawainese because there are soundsthat unusual used in Minangkabau language, for example [ə] and [ɤ]. Furthemore, The variation is not change the meaning at all.